Pengaruh Pembelajaran Berbasis HOTS dan Gaya Belajar terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Yeyen Wahyuni; Nafan Tarihoran; Diki (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
This study aims to analyze the effect of HOTS-based learning and learning styles on students’ mathematics learning outcomes. This study employed a quantitative, quasi-experimental design. The participant consisted of fifth-grade students from public elementary schools in Kalanganyar District, selected through purposive sampling. The results indicate that HOTS-based learning has a positive and significant effect on mathematics learning outcomes, learning styles also have a significant effect, and there is an interaction between HOTS-based learning and learning styles on students’ learning outcomes. The findings suggest that implementing HOTS-based learning aligned with students’ learning styles can enhance the effectiveness of mathematics instruction in elementary schools.